Overcoming the monster: How vulnerable small businesses turn rival villains into co-branded storytelling heroes - Maritha Pritchard; Abyshey Nhedzi; Auguste Fabian (Innovar: Revista de Ciencias Administrativas y Sociales)
Storytelling is a popular and effective brand building approach among prominent consumer brands. But for vulnerable small businesses focused on daily survival, the thought of pursuing a brand alliance partner and telling their co-brand stories on social media may be taking one business risk too many. Not knowing where to begin when seeking suitable Business-to-Business (B2B) partners or how even to find stories to tell, community entrepreneurs may evade potential growth opportunities out of fear of rivals competing for the same scarce resources. The purpose of this study was to explore how resource-dependent Small Medium Enterprises (SMEs) use co-branded storytelling strategies to build B2B brands on Facebook. Findings from an exploratory sequential mixed-methods study gathering data from a purposive sample of small businesses recommend several joint venture strategies for SMEs scared to venture into co-branding. The study's unique contribution is a description of four co-branded story plots and their possible narrative variations. Results suggest that regional B2B clusters benefit from co-branded endorsements by collectively establishing a competitive critical mass for community-based enterprises. Culturally relatable co-branded stories have a competitive edge over their large, retail counterparts when innovatively leveraging authentic stories intimately depicting the local flavours and unique neighbourhood characters in emotionally provocative story plots.